PENGARUH FINANCIAL DISTRESS TERHADAP MANAJEMEN LABA DENGAN MODERASI CORPORATE GOVERNANCE - Calvin Ivanoko Novara Tannaya; Lodovicus Lasdi (Universitas Katolik Widya Mandala Surabaya, 2021)
Earnings management is often carried out by companies that are experiencing going concern problems. Earnings management is often associated with the act of manipulating financial statements that can harm shareholders. In overcoming these problems, corporate governance is often used to prevent earnings management practices and be able to provide accountable financial reports. Through this study, we will see and analyze how the effect of financial distress on the possibility of earnings management by moderating corporate governance mechanisms. Manufacturing companies on the IDX with the period 2015 to 2019 were chosen as objects for analysis in this study. The data obtained were processed using multiple linear regression techniques. This study produces several conclusions, First there is no influence of financial distress variables and company size on earnings management. Furthermore, it is found that independent commissioners can moderate the relationship between financial distress and earnings management, but it does not apply to the audit committee.